Carbon-paper-loaded sulfur-vacancy-rich ternary heterostructure intermediate layer and preparation method and application of carbon-paper-loaded sulfur-vacancy-rich ternary heterostructure intermediate layer
By using carbon paper to load the ternary heterostructure intermediate layer of MoS2-x/MoO2/CoP with sulfur-rich vacancies in lithium-sulfur batteries, the chaotic migration of lithium polysulfide and slow redox reaction kinetics are solved. Problem, significantly improving the performance and cycle stability of the battery.
Patent Information
- Application Number
- CN202411485875.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The chaotic migration of lithium polysulfide, slow redox reaction kinetics and obvious shuttle effects of lithium sulfur batteries lead to capacity attenuation and low Coulomb efficiency, hindering the practical application of lithium sulfur batteries.
The ternary heterostructure intermediate layer of MoS2-x/MoO2/CoP loaded with sulfur-rich vacancy was adopted. It was synthesized by a two-step hydrothermal-phosphorization method to form a spontaneous built-in electric field and highly adsorptive structure to enhance the polysulfide capture capability and redox reaction kinetics.
It significantly improves the polysulfide capture capability and redox reaction kinetics of lithium-sulfur batteries, extends the cycle life of the battery, and realizes a lithium-sulfur battery with stable long-term performance.
Smart Images

Figure CN119400793A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation and catalyst, and specifically relates to a carbon paper-loaded sulfur vacancy-rich ternary heterostructure intermediate layer and a preparation method and application thereof. Background Art
[0002] With the increasing popularity of portable electronic devices and electric vehicles in daily life, the limited theoretical energy density of lithium-ion batteries cannot meet the rapidly developing social needs. Lithium-sulfur batteries (LSBs) have high theoretical energy density and capacity and are considered to be promising next-generation energy storage systems. Compared with lithium-ion batteries, LSBs have the advantages of low cost, environmental sustainability, and abundant resources. However, the poor conductivity of sulfur and its discharge products leads to low sulfur utilization; in addition, the shuttle effect caused by soluble lithium polysulfides (LiPSs) and the slow sulfur redox kinetics lead to severe capacity decay and low Coulombic efficiency, which hinders the practical application of LSBs.
[0003] To address these issues, researchers have developed advanced catalytic materials, including heteroatom-doped carbon materials, transition metals and metal oxides / sulfides and their composites, aimed at adsorbing polysulfides and reducing the reaction barriers of polysulfides. Although some progress has been made, integrating the individual functions of each component (including abundant catalytic active sites, enhanced chemical adsorption, high conductivity and high Li + However, the diffusion of LiPSs is still challenging, resulting in suboptimal catalytic activity. Especially under the conditions of high sulfur loading and low electrolyte sulfur ratio, it is still difficult to effectively alleviate the shuttle effect of LiPSs and improve the sluggish redox reaction kinetics.
[0004] Recently, the emergence of heterostructures has effectively overcome these challenges. Studies have shown that heterostructures formed by nanomaterials with different work functions can generate spontaneous built-in electric fields (BIEFs), thereby enhancing electron / ion transport and surface reaction kinetics. In addition, heterostructures can also comprehensively improve electron transport, redox kinetics, and lithium ion adsorption through the synergistic enhancement effect of each component.
[0005] On the one hand, the stable charge distribution in the defect-free crystal structure limits the polar interactions between LiPSs and the lithiophilic surface. The introduction of sulfur vacancies in metal sulfides can break the charge balance, thereby improving the charge transfer kinetics and catalytic activity. The active electrons around the sulfur vacancies facilitate chemical adsorption with LiPSs to form strong covalent bonds. In addition, S n 2-The mobility determines the movement of electrons / ions, and the movement of electrons / ions is affected by positive and negative charges and causes relative displacement.
[0006] Some heterostructure catalysts have low catalytic activity in sulfur reduction and oxidation reactions, resulting in low reaction efficiency. The conductivity of the heterostructure may be insufficient, affecting electron conduction and thus reducing the overall performance of the battery. During the charge and discharge process, some catalysts may degrade or deactivate, affecting the cycle life of the battery. In addition, there may be instability at the interface between different materials in the heterostructure, resulting in reduced catalytic performance. The preparation of high-performance heterostructure catalysts usually requires complex synthesis steps, which increases production costs and difficulty. Summary of the invention
[0007] In response to the problems of chaotic migration of lithium polysulfide, slow redox reaction kinetics and obvious shuttling effect in lithium-sulfur batteries, the present invention proposes a method for preparing a carbon paper-loaded ternary heterostructure intermediate layer rich in sulfur vacancies, which further enhances the material's ability to capture polysulfides and promotes their directional migration, while having fast redox reaction kinetics and excellent long-cycle stability.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] On the one hand, the present invention provides a carbon paper-loaded MoS rich in sulfur vacancies. 2-x The method for preparing a / MoO2 / CoP ternary heterostructure intermediate layer comprises the following steps:
[0010] S1: Dissolve ammonium molybdate tetrahydrate and thiourea in deionized water, add ZIF-67, stir and mix well, and immerse carbon paper in the mixed solution;
[0011] S2: The mixed solution obtained in step S1 is subjected to a hydrothermal reaction, washed, and dried to obtain carbon paper-supported MoS2 / Co 1.2 MoO 4.2 1.3H2O precursor;
[0012] S3: placing the precursor obtained in step S2 into a ceramic ark at the rear end of a tube furnace, placing sodium hypophosphite at the front end of the tube furnace, and calcining in a mixed gas atmosphere of hydrogen and inert gas to obtain the carbon paper-loaded MoS rich in sulfur vacancies. 2-x / MoO2 / CoP ternary heterostructure intermediate layer.
[0013] In the above technical solution, further, in step S1, the preparation method of ZIF-67 comprises the following steps:
[0014] (1) Dissolve Co(NO3)2·6H2O in a methanol solution to obtain solution A, and dissolve 2-methylimidazole in an equal volume of a methanol solution to obtain solution B;
[0015] (2) Pour solution A into solution B to obtain a cobalt organic complex ZIF-67 precursor solution, mature, centrifuge, and dry to obtain ZIF-67.
[0016] In the above technical solution, further, the molar ratio of Co(NO3)2·6H2O to 2-methylimidazole is 1:4.
[0017] In the above technical solution, further, in step S1, the molar ratio of ammonium molybdate tetrahydrate to thiourea is 1:2; the molar ratio of ammonium molybdate tetrahydrate to ZIF-67 is 1:10.
[0018] In the above technical solution, further, in step S2, the temperature of the hydrothermal reaction is 190-220°C, and the time is 20-24h; the temperature of the drying is 60-80°C, and the time is 6-12h.
[0019] In the above technical scheme, further, in step S3, the molar ratio of ammonium molybdate tetrahydrate to sodium hypophosphite is 1:6; the inert gas is one or both of nitrogen and argon; the calcination temperature is 700-800°C, the insulation time is 1-3h, and the heating rate is 3-6°C / min.
[0020] Another aspect of the present invention provides a carbon paper loaded with sulfur vacancy-rich MoS prepared by the above preparation method. 2-x / MoO2 / CoP ternary heterogeneous structure middle layer, the middle layer is based on carbon paper, and the surface is loaded with Mo S 2-x / MoO2 / CoP, the MoS 2-x / MoO2 / CoP is in the shape of nanoflowers, which are formed by interconnected nanosheets.
[0021] The present invention also provides a carbon paper loaded with MoS rich in sulfur vacancies. 2-x Application of / MoO2 / CoP ternary heterostructure interlayer in lithium-sulfur batteries.
[0022] The carbon paper of the present invention supports MoS rich in sulfur vacancies 2-x / MoO2 / CoP ternary heterostructure intermediate layer was synthesized by hydrothermal-phosphating two-step method. Firstly, MoS2 / Co 1.2 MoO 4.2 ·1.2H2O binary heterostructures are deposited on carbon paper substrates, during which thiourea (CH4N2S) sulfides ammonium molybdate tetrahydrate (H 32 Mo7N6O 28) generates MoS2, MoO4 2- With Co 2+ The reaction produces Co 1.2 MoO 4.2 Finally, MoS2 / Co 1.2 MoO 4.2 1.2H2O phosphating in Ar / H2 atmosphere to generate MoS with sulfur vacancies 2-x / MoO2 / Co P, during the phosphating process, Co 1.2 MoO 4.2 ·1.2 The MoO3 in H2O cannot be phosphated but is reduced to MoO2 by the carbon in thiourea.
[0023] The present invention forms a heterogeneous structure for spontaneously generating BIEF by pairing an adsorbent with high adsorption and high work function with a catalyst with medium adsorption, low work function and high catalytic activity, and introducing an intermediate catalyst with excellent electronic conductivity and medium work function. The introduction of vacancies in the adsorbent can further enhance its adsorption capacity. Under the synergistic effect of the BIEF electric field and sulfur vacancies, the migration of electrons from the catalyst to the adsorbent is enhanced, which in turn promotes the capture of LiPSs and promotes the Sn 2- Directed migration towards the catalyst, thus achieving efficient catalytic conversion.
[0024] The beneficial effects of the present invention are:
[0025] (1) The carbon paper of the present invention is loaded with MoS rich in sulfur vacancies 2-x The intermediate layer of the / MoO2 / CoP ternary heterostructure was synthesized by a two-step hydrothermal-phosphating method. First, a uniform precursor was obtained by a hydrothermal method, and the binary heterostructure was loaded on a carbon paper substrate. Then, the intermediate layer was stabilized by carbonization and sulfur reduction to form MoS rich in sulfur vacancies through a high-temperature phosphating calcination process. 2-x / MoO2 / CoP ternary heterostructure, the material has a unique ternary heterojunction nanoflower morphology, and various elements are evenly distributed in the material. At the same time, the nanoflower is formed by interconnected nanosheets with a thickness of 2-10nm, which can effectively increase the contact area between the material and the active substance, expose more active sites, improve the material's adsorption capacity for polysulfides, and further improve the redox reaction kinetics of sulfur species.
[0026] (2) MoS rich in sulfur vacancies of the present invention 2-x / MoO2 / CoP ternary heterostructure due to the different work functions of each component (CoP (4.93eV) <MoS 2-x / MoO2 / CoP (5.19 eV) < MoO2 (5.27 eV) < MoS2 / MoO2 / CoP (5.30 eV) < MoS2 (5.39 eV)), thus forming a spontaneous built-in electric field. Sulfur vacancies enhance the adsorption force between MoS 2-x and polysulfides, resulting in the preliminary aggregation of S n 2- ions on the MoS 2-x surface. Meanwhile, driven by the built-in electric field, the aggregated S n 2- ions migrate directionally towards the heterojunction interface and reach the CoP surface for subsequent phase transformation. Under the synergistic effect of sulfur vacancies and the heterojunction structure, the shuttle effect of LiPSs is inhibited, and the catalytic conversion of sulfur species is accelerated, thereby realizing the stepwise conversion of sulfur and achieving a practical lithium-sulfur battery with long-term stable performance. Brief Description of the Drawings
[0027] The invention is further described with reference to the accompanying drawings. However, the embodiments in the drawings do not constitute any limitation to the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained according to the following drawings.
[0028] Figure 1 Scanning electron microscopy and transmission electron microscopy images of the intermediate layer sample prepared in Example 1. (a) is the scanning electron microscopy image, (b) is the TEM image, (c) is the HRTEM image, (d)-(f) are the magnified regions of the HRTEM image, (g) is the high-angle annular dark-field image, and (h)-(m) are the elemental maps;
[0029] Figure 2 Physical structure characterization of the intermediate layer samples prepared in Example 1 and Comparative Example 1. (a) is the X-ray diffraction spectrum, (b) is the magnified X-ray diffraction spectrum based on the MoS2 (002) plane, (c) is the Mo3d X-ray photoelectron spectrum, (d) is the Raman spectrum, (e) is the magnified Raman spectrum, (f) is the electron paramagnetic resonance test spectrum, and (g) is the energy band diagram of the MoS 2-x / MoO2 / CoP ternary heterostructure before and after the formation of the built-in electric field contact. (h) is the charge difference within MoS 2-x / MoO2 / CoP;
[0030] Figure 3CV curves of lithium-sulfur batteries assembled with the intermediate layers of Example 1 and Comparative Examples 1-4 and test results of lithium ion diffusion rates, (a) is the CV curve of Example 1, (b) is the CV curve of Comparative Example 1, (c) is the CV curve of Comparative Example 2, (d) is the CV curve of Comparative Example 3, (e) is the CV curve of Comparative Example 4, (f) is the peak I fitting curve, (g) is the peak II fitting curve, (h) is the peak III fitting curve, and (i) is a bar graph of lithium ion diffusion rate results;
[0031] Figure 4 The sulfur deposition diagrams of the assembled lithium-sulfur batteries using the intermediate layers of Example 1 and Comparative Examples 1-4 are shown in Figures 1-4, (a) is Example 1, (b) is Comparative Example 1, (c) is Comparative Example 2, (d) is Comparative Example 3, and (e) is Comparative Example 5;
[0032] Figure 5 The UV adsorption diagram of the assembled lithium-sulfur battery using the intermediate layer of Example 1 and Comparative Examples 1-4;
[0033] Figure 6 The performance graphs are of the battery performance test results of the assembled lithium-sulfur battery using the intermediate layer of Example 1 and Comparative Examples 1-4, (a) is the AC impedance graph, (b) is the cycle performance at 0.2C, (c) is the charge and discharge curve at 0.2C, (d) is the rate performance, (e) is the cycle performance at different S loads at 0.2C, and (f) is the long-term cycle performance of 1000 cycles at 2C. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0035] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Example 1
[0037] A carbon paper loaded with sulfur vacancy-rich MoS 2-x The method for preparing a / MoO2 / CoP ternary heterostructure intermediate layer comprises the following steps:
[0038] S1: 1.485 g Co(NO3)2·6H2O was dissolved in 50 mL methanol solution, recorded as solution A, 1.64 g 2-methylimidazole was dissolved in 50 mL methanol solution, obtained solution B, solution A was slowly poured into solution B to obtain the cobalt organic complex ZIF-67 precursor solution, aged for 24 h, and finally, 9000 r min -1 ZIF-67 was separated by centrifugation (10 min), dried overnight and set aside;
[0039] S2: Carbon paper cut into 16 mm diameter discs;
[0040] S3: Dissolve 0.6 g of ammonium molybdate tetrahydrate and 0.38 g of thiourea in 30 ml of deionized water, then add 0.1 g of ZIF-67, stir and mix well, and immerse the carbon paper disc in the mixed solution;
[0041] S4: The mixed solution obtained in S3 is placed in a hydrothermal reactor, and the reaction temperature is 200°C. After the hydrothermal reaction for 20 hours, it is washed and dried to obtain MoS2 / Co supported on carbon paper. 1.2 MoO 4.2 1.3H2O precursor;
[0042] S5: The precursor obtained in S4 is placed in a ceramic ark and placed at the rear end of the tube furnace. 0.6 g of sodium hypophosphite is placed at the front end of the tube furnace. In an Ar / H2 inert atmosphere with a H2 volume concentration of 10%, the temperature is increased to 750°C at a heating rate of 3°C / min and kept at this temperature for 2 hours for phosphating calcination and high-temperature reduction to obtain a carbon paper-loaded ternary heterostructure intermediate layer rich in sulfur vacancies.
[0043] Comparative Example 1
[0044] A method for preparing a carbon paper-loaded MoS2 / MoO2 / CoP ternary heterostructure intermediate layer rich in sulfur vacancies and free of sulfur vacancies comprises the following steps:
[0045] S1: 1.485 g Co(NO3)2·6H2O was dissolved in 50 mL methanol solution, recorded as solution A, 1.64 g 2-methylimidazole was dissolved in 50 mL methanol solution, obtained solution B, solution A was slowly poured into solution B to obtain the cobalt organic complex ZIF-67 precursor solution, aged for 24 h, and finally, 9000 r min -1 ZIF-67 was separated by centrifugation (10 min), dried overnight and set aside;
[0046] S2: Carbon paper cut into 16 mm diameter discs;
[0047] S3: Dissolve 0.6 g of ammonium molybdate tetrahydrate and 0.38 g of thiourea in 30 ml of deionized water, then add 0.1 g of ZIF-67, stir and mix well, and immerse the carbon paper disc in the mixed solution;
[0048] S4: The mixed solution obtained in S3 was placed in a hydrothermal reactor, and the reaction temperature was 200°C. After the hydrothermal reaction for 20 hours, it was washed and dried to obtain MoS2 / Co supported on carbon paper. 1.2 MoO 4.2 1.3H2O precursor;
[0049] S5: Place the precursor obtained in S4 into a ceramic ark and place it at the rear end of the tube furnace. Take 0.6 g of sodium hypophosphite and place it at the front end of the tube furnace. Under an Ar inert atmosphere, heat the temperature to 750°C at a heating rate of 3°C / min and keep it warm for 2 hours for phosphating calcination to obtain a carbon paper-loaded MoS2 / MoO2 / CoP ternary heterostructure intermediate layer free of sulfur vacancies.
[0050] Comparative Example 2
[0051] A method for preparing a carbon paper-loaded MoS2 intermediate layer comprises the following steps:
[0052] S1: 1.485 g Co(NO3)2·6H2O was dissolved in 50 mL methanol solution, recorded as solution A, 1.64 g 2-methylimidazole was dissolved in 50 mL methanol solution, obtained solution B, solution A was slowly poured into solution B to obtain the cobalt organic complex ZIF-67 precursor solution, aged for 24 h, and finally, 9000 r min -1 ZIF-67 was separated by centrifugation (10 min), dried overnight and set aside;
[0053] S2: Carbon paper cut into 16 mm diameter discs;
[0054] S3: Dissolve 0.49 g of ammonium molybdate tetrahydrate and 0.38 g of thiourea in 30 ml of deionized water, then add 0.1 g of ZIF-67, stir and mix well, and immerse the carbon paper disc in the mixed solution;
[0055] S4: The mixed solution obtained in S3 is placed in a hydrothermal reactor, and after a hydrothermal reaction at a reaction temperature of 200° C. for 20 hours, it is cleaned and dried to obtain MoS2 supported on carbon paper.
[0056] Comparative Example 3
[0057] A method for preparing a carbon paper-loaded MoO2 intermediate layer comprises the following steps:
[0058] S1: Commercial MoO3 powder was used as the precursor, which was ultrasonicated for 2 h and then drop-cast onto carbon paper;
[0059] S2: MoO2 was prepared by chemical vapor reduction method, and carbon paper with MoO3 drop-cast was placed in the middle of the quartz tube;
[0060] S3: The reaction was carried out at 750 °C in an Ar / H2 mixed atmosphere for 3 h, during which H2 was used as a reducing agent to obtain carbon paper-supported MoO.
[0061] Comparative Example 4
[0062] S1: Dissolve 1.485 g Co(NO3)2·6H2O in 30 ml methanol to obtain solution A, and dissolve 1.64 g 2-methylimidazole in 30 ml methanol to obtain solution B;
[0063] S2: Carbon paper cut into 16 mm diameter discs;
[0064] S3: Pour solution A into solution B, then add the carbon paper disc, and continue stirring the mixture for 24 hours;
[0065] S4: In an Ar environment, carbon paper loaded with 0.3 g of sodium hypophosphite and in-situ grown ZIF-67 was heated at 750°C for 3 h to allow CoP to grow in situ on the carbon paper, thereby obtaining carbon paper-supported CoP.
[0066] Figure 1 The scanning electron microscope and transmission electron microscope images of the intermediate layer sample prepared in Example 1, MoS 2-x / MoO2 / CoP exhibits a typical nanoflower structure morphology, consisting of ultrathin nanosheets with a thickness of 2-10nm ( Figure 1 (a)), which is beneficial to expose more active sites and accelerate electron transfer. Figure 1 TEM analysis shown in (b) further demonstrates the details of the interconnection and uniform distribution of the nanosheets. High-resolution TEM (HRTEM) image ( Figure 1 (c)) and the corresponding magnified HR-TEM image ( Figure 1 (d)-(f)) show that the lattice spacings are 0.65, 0.281, and 0.173 nm, corresponding to the (002) crystal plane of MoS2, the (101) crystal plane of MoO2, and the (103) crystal plane of CoP, respectively. This indicates that MoS 2-x There are many heterostructure interfaces in / MoO2 / CoP. Figure 1 (g)-(m) MoS 2-x The energy-dispersive X-ray spectroscopy of / MoO2 / CoP shows the uniform distribution of C, Mo, S, O, Co and P, further confirming the coexistence of MoS2, MoO2 and CoP.
[0067] Figure 2The physical structure characterization of the intermediate layer samples prepared in Example 1 and Comparative Example 1 is as follows: Figure 2 As shown in (a), in MoS rich in sulfur vacancies 2-x The characteristic peaks of MoS2, CoP and MoO2 were found in MoS2 / MoO2 / CoP and MoS2 / MoO2 / CoP without sulfur vacancies, which confirmed the successful synthesis of the ternary heterostructure. 2-x After high-temperature reduction treatment, the (002) peak of / MoO2 / CoP slightly shifted to a lower angle (14.2°→14.1°, Figure 2 (b)), while the positions of other characteristic peaks remain unchanged, which indicates that MoS2 is reduced and MoS 2-x Sulfur vacancies are generated inside / MoO2 / CoP. X-ray photoelectron spectroscopy (XPS) was used to characterize the MoS 2-x The surface chemical composition, element valence states and interfacial interactions of MoS / MoO2 / CoP were characterized. 2-x / MoO2 / CoP and MoS2 / MoO2 / CoP in high-resolution Mo 3d spectra ( Figure 2 (c)), the peaks at 229.1eV and 232.4eV are attributed to Mo, respectively. 4+ 3d 5 / 2 and Mo 4 + 3d 3 / 2 , while the other peak at 226.2 eV was identified as S2s. Compared with MoS2 / MoO2 / CoP, MoS 2-x Mo3d in / MoO2 / CoP 5 / 2 and 3D 3 / 2 The peak shifts to lower binding energy, indicating that the electron cloud density around Mo increases and the oxidation degree of Mo state decreases. This shift promotes the electron transfer from CoP to MoS 2-x and accelerate the transfer of LiPSs in MoS 2-x / MoO2 / CoP directional transmission. Raman spectrum shows 281, 375, 403 and 451 cm -1 Shoulder straps, Figure 2 (d) is attributed to the stretching mode of MoS2. 990cm -1 The Raman modes at 741 and 813 cm are related to the stretching vibration of PO in the disordered system, indicating the presence of CoP. -1 The two weak bands centered at are the characteristics of MoO2 and MoO3 respectively. 2-x A blue shift appeared in the Raman spectrum after reduction, indicating that MoS 2-xThe desulfurization produced atomic rearrangement and structural strain. This changed the Mo-S-Mo bond length and the corresponding crystal parameters, indicating that after H2 reduction, MoS 2-x / MoO2 / CoP forms sulfur vacancies ( Figure 2 (e)). In addition, MoS 2-x The electron paramagnetic resonance (EPR) spectra of MoS2 / MoO2 / CoP and MoS2 / MoO2 / CoP also confirmed this observation. 2-x The EPR signal intensity of / MoO2 / CoP at g = 2.004 is significantly higher than that of MoS2 / MoO2 / CoP, indicating that the sulfur vacancy content is higher ( Figure 2 (f)). In summary, these tests confirm the successful synthesis of ternary heterostructures with sulfur vacancies via hydrothermal reaction and high-temperature H2 reduction.
[0068] Figure 2 (g) MoS before and after the formation of built-in electric field contact 2-x Energy band diagram of the ternary heterostructure of E / MoO2 / CoP, vac is the vacuum layer, E c is the lowest energy band, E f is a flat energy band, E v is the valence band, such as Figure 2 As shown in (g), due to their different work functions, electrons are transferred from CoP to MoO2 and then to MoS2 until the three materials reach the same Fermi level. 2-x The work function of / MoO2 / CoP is between CoP, MoO2 and MoS2, which indicates that the introduction of sulfur vacancies reduces its work function and thus accelerates the electron transfer speed.
[0069] Figure 2 The charge density difference model in (h) shows the MoS 2-x The obvious charge transfer between MoO2 and CoP further confirms the ternary heterostructure (CoP→MoO2→MoS 2-x ) is reasonable for the electron transfer pathway.
[0070] Figure 3 The CV curves and lithium ion diffusion rate test results of the lithium-sulfur battery assembled with the intermediate layer of Example 1 and Comparative Examples 1-4 are shown. The diffusion rate of lithium ions is a key factor affecting the kinetics of polysulfide redox reactions. Cyclic voltammetry (CV) experiments were performed using a Bio-Logic VMP3 electrochemical workstation with a voltage range of 1.7 to 2.8 V. The results were obtained by measuring the diffusion rate of lithium ions at 0.1 to 0.5 mV s -1 The cyclic voltammetry (CV) curves obtained at a scan rate of Figure 3(a)-(e) are used to evaluate the diffusion capacity and reaction kinetics of lithium ions during phase transition. Linear regression analysis between peak current and square root of scan rate was performed for each curve ( Figure 3 (f)-(h)). The diffusion rate of lithium ions is calculated based on the Randles-Sevcik equation. Figure 3 The calculation results of MoS 2-x / MoO2 / CoP at each stage of the redox reaction (peak I: from solid Li2S to liquid Li2S n ; Peak II: from solid S8 to liquid Li2S4; Peak III: from liquid Li2S4 to solid Li2S) has a larger lithium ion diffusion coefficient. This shows that MoS 2-x The sulfur vacancies and built-in electric field in / MoO2 / CoP synergistically accelerate the diffusion rate of lithium ions and improve the conversion kinetics of polysulfides.
[0071] In order to study MoS 2-x The liquid-to-solid phase transition capability of / MoO2 / CoP was investigated by Li2S deposition, and the conversion of soluble LiPSs to insoluble Li2S was tested by constant voltage discharge at 2.05 V, using Li2S8 solution as the cathode electrolyte. Figure 4 As shown in (a)-(e), MoS 2-x / MoO2 / CoP showed the highest precipitation capacity (176.1 mAh g -1 ) and the fastest initial nucleation time (1580s). Therefore, MoS 2-x The obvious nucleation of Li2S observed in / MoO2 / CoP indicates that it can effectively enhance the liquid-solid transition kinetics between LiPSs and Li2S. The above analysis shows that the deposition and decomposition of Li2S are closely related to the MoS 2-x / MoO2 / CoP is more favorable on the surface, promoting the efficient conversion and recovery of sulfur.
[0072] Figure 5 The UV adsorption diagram of the assembled lithium-sulfur battery using the intermediate layer of Example 1 and Comparative Examples 1-4 shows that the MoS 2-x The Li2S6 solution of / MoO2 / CoP shows the weakest characteristic peak at 410nm, indicating a strong affinity between the heterojunction and Li2S6.
[0073] Figure 6 The performance graph is a performance graph of the battery performance test results of the lithium-sulfur battery assembled using the intermediate layer of Example 1 and Comparative Examples 1-4. Figure 6 In (a), MoS 2-xThe electrochemical impedance spectroscopy (EIS) results of MoS / MoO2 / CoP, MoS2 / MoO2 / CoP, MoS2, MoO2, and CoP show a semicircle in the high- to medium-frequency range and a slanted line in the low-frequency range. 2-x / MoO2 / CoP has the smallest semicircle diameter and the lowest Warburg impedance (highest slope), which indicates that it has the dual advantages of low charge transfer resistance and excellent electrochemical kinetics. Figure 6 (b) shows that at 0.2C, MoS 2-x The battery with the / MoO2 / CoP intermediate layer has the best performance and the highest initial specific capacity, reaching 1356.2 mAh g -1 After 400 cycles, the battery capacity remained at 1015.1 mA hg -1 , with the lowest attenuation rate of only 0.062%. In contrast, the initial specific capacities of the battery using the MoS2 / MoO2 / CoP interlayer (without sulfur vacancies) and the battery using single-component MoS2, MoO2, or CoP interlayers were lower (1259.9, 942.1, 815.6, and 1103.7 mAh g -1 ). In addition, their capacity decay rates increase with the increase of cycle number (0.086%, 0.077%, 0.077%, and 0.088%, respectively). Figure 6 (c) shows the electrochemical charge-discharge curves, which have two characteristic discharge plateaus and an obvious charge plateau. 2-x The cell polarization voltage gap of the / MoO2 / CoP interlayer is reduced and the second discharge platform is prolonged, indicating that the redox reaction is faster and more reversible. 2-x / MoO2 / CoP showed reduced deposition and dissociation overpotentials, highlighting their catalytic role in reducing the reaction barriers. Figure 6 As shown in (d), MoS 2-x The battery with / MoO2 / CoP interlayer has the highest discharge specific capacity at different current densities (0.2, 0.5, 1, 2, 3, and 4C), which are 1370.2, 1137.7, 1053.7, 881.3, 717.7, and 656.7 mAh g, respectively. -1 When the current density returned to 0.2C, the discharge capacity was still 1270.1mAh g -1 , and maintained stable performance in subsequent cycles, thus demonstrating excellent electrochemical reversibility. Figure 6 (e) Performance of LSBs with different sulfur loadings at 0.2C. When the sulfur loading reaches 7.13 mg cm -2 When MoS 2-xThe electrode with / MoO2 / CoP interlayer showed 7.2 mAh cm -2 After 100 cycles, the capacity stabilized at 6.6 mAh cm -2 , which is equivalent to a retention rate of 91.7%. This excellent stability at high sulfur loading indicates that MoS 2-x / MoO2 / CoP heterostructure is a feasible interlayer material for practical LSBs applications. Figure 6 As shown in (f), MoS 2-x The battery with / MoO2 / CoP interlayer has 930.6 mAh g -1 The capacity is still maintained at 708.3 mAh g after 1000 cycles at 2C. -1 This corresponds to a low decay rate of 0.02% per cycle.
[0074] The reversible capacity and decay rate of the carbon paper-loaded sulfur vacancy-rich ternary heterojunction interlayer of the present invention at high sulfur loading exceed those of most reported LSBs, as shown in Table 1. Compared with commercial lithium-sulfur batteries, the carbon paper-loaded MoS 2-x Lithium-sulfur batteries with a / MoO2 / CoP ternary heterojunction interlayer show higher average capacity, demonstrating their excellent development potential and commercial prospects.
[0075] Table 1 Comparison of the performance of the assembled lithium-sulfur battery using the intermediate layer of Example 1 under high sulfur loading with published literature
[0076]
[0077]
[0078] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A carbon paper loaded with MoS rich in sulfur vacancies 2-x / MoO2 / CoP ternary heterostructure intermediate layer preparation method, characterized in that, The following steps are involved: S1: Dissolve ammonium molybdate tetrahydrate and thiourea in deionized water, add ZIF-67, stir and mix well, and immerse carbon paper in the mixed solution; S2: The mixed solution obtained in step S1 is subjected to a hydrothermal reaction, washed, and dried to obtain carbon paper-supported MoS2 / Co 1.2 MoO 4.2 1.3H2O precursor; S3: placing the precursor obtained in step S2 into a ceramic ark at the rear end of a tube furnace, placing sodium hypophosphite at the front end of the tube furnace, and calcining in a mixed gas atmosphere of hydrogen and inert gas to obtain the carbon paper-loaded MoS rich in sulfur vacancies. 2-x / MoO2 / CoP ternary heterostructure intermediate layer.
2. The preparation method according to claim 1, characterized in that: In step S1, the preparation method of ZIF-67 comprises the following steps: (1) Dissolve Co(NO3)2·6H2O in a methanol solution to obtain solution A, and dissolve 2-methylimidazole in an equal volume of a methanol solution to obtain solution B; (2) Pour solution A into solution B to obtain a cobalt organic complex ZIF-67 precursor solution, mature, centrifuge, and dry to obtain ZIF-67.
3. The preparation method according to claim 2, characterized in that: The molar ratio of Co(NO3)2·6H2O to 2-methylimidazole is 1:
4.
4. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of ammonium molybdate tetrahydrate to thiourea is 1:2; The molar ratio of ammonium molybdate tetrahydrate to ZIF-67 is 1:
10.
5. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 190-220°C and the time is 20-24h; The drying temperature is 60-80°C and the drying time is 6-12 hours.
6. The preparation method according to claim 1, characterized in that: In step S3, the molar ratio of ammonium molybdate tetrahydrate to sodium hypophosphite is 1:6; The inert gas is one or both of nitrogen and argon; The calcination temperature is 700-800°C, the heat preservation time is 1-3h, and the heating rate is 3-6°C / min.
7. A carbon paper loaded with MoS rich in sulfur vacancies prepared by the preparation method according to any one of claims 1 to 6 2-x / MoO2 / CoP ternary heterostructure intermediate layer, characterized in that: The intermediate layer is based on carbon paper and the surface is loaded with MoS 2-x / MoO2 / CoP, the MoS 2-x / MoO2 / CoP is in the shape of nanoflowers, which are formed by interconnected nanosheets.
8. A carbon paper loaded with sulfur vacancy-rich MoS according to claim 7 2-x Application of / MoO2 / CoP ternary heterostructure interlayer in lithium-sulfur batteries.
Citation Information
Patent Citations
Wire structure carbon fiber / MoS2 / MoO2 flexible electrode material and preparation method thereof
CN107221635A
Lithium-sulfur battery positive electrode material and preparation method thereof, lithium-sulfur battery positive plate and lithium-sulfur battery
CN116332232A
CoMoO4-CoP heterojunction / hollow polyhedral N-doped carbon skeleton composite material and preparation method and application thereof
CN116603554A
Device for generating aerosol
KR1020230142254A
Method of forming a layer by ald
KR1020240178687A